CITRONELLA AGROFORESTRY IN GAYO LUES REGENCY OF INDONESIA - Fitrah M.S.; Hamid A.H.; Romano (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
An agroforestry practice system has been applied by Gayo Lues community in managing their agricultural land. The most dominant tree species treated by farmers among the citronella plants is pine. The population in this study was 2,403 farmers. From the total population, samples were taken by using Slovin formula so that the sample became 96 farmers. The agroforestry system in Gayo Lues Regency uses a blend of pine trees (woody plants) with citronella plants (non-woody plants). The optimal area of citronella agroforestry for farmers is 1.3 ha. They have fulfilled the needs of a decent living in this area.